Presence of Fe(II) and nitrate shapes aquifer-originating communities leading to an autotrophic enrichment dominated by an Fe(II)-oxidizing Gallionellaceae sp. Issue 11 (1st November 2021) - Jakus, Natalia; Blackwell, Nia; Straub, Daniel; Kappler, Andreas; Kleindienst, Sara
ABSTRACT: Autotrophic nitrate reduction coupled to Fe(II) oxidation is an important nitrate removal process in anoxic aquifers. However, it remains unknown how changes of O2 and carbon availability influence the community structure of nitrate-reducing Fe(II)-oxidizing (NRFeOx) microbial assemblages and what the genomic traits of these NRFeOx key players are. We compared three metabolically distinct denitrifying assemblages, supplemented with acetate, acetate/Fe(II) or Fe(II), enriched from an organic-poor, pyrite-rich aquifer. The presence of Fe(II) promoted the growth of denitrifying Burkholderiaceae spp. and an unclassified Gallionellaceae sp. This Gallionellaceae sp. was related to microaerophilic Fe(II) oxidizers; however, it did not grow under microoxic conditions. Furthermore, we explored a metagenome and 15 metagenome-assembled genomes from an aquifer-originating, autotrophic NRFeOx culture. The dominant Gallionellaceae sp. revealed the potential to oxidize Fe(II) (e.g. cyc2 ), fix CO2 (e.g. rbcL ) and perform near-complete denitrification leading to N2 O formation (e.g. narGHJI, nirK/S and norBC ). In addition, Curvibacter spp., Methyloversatilis sp. and Thermomonas spp. were identified as novel putative NRFeOx taxa. Our findings provide first insights into the genetic traits of the so far only known autotrophic NRFeOx culture originating from an organic-poor aquifer, providing the genomic basis to study mechanisms of nitrate removal in organic-poor subsurface ecosystems. Abstract : Nitrate in organic-poor aquifers can be removed by autotrophic Fe(II)-oxidizing communities, dominated by microorganisms belonging to the family Gallionellaceae.